Validity and psychometric characteristics of the self-administered comorbidity questionnaire in patients with psoriatic arthritis - DURUÖZ, MEHMET TUNCAY (My University, 2022)
The study aimed to translate and cross-culturally adapt the self-comorbidity questionnaire (SCQ) into Turkish and investigate the validity and reliability of SCQ and its modified version (mSCQ) in psoriatic arthritis (PsA). Psoriatic arthritis quality of life (PsAQoL) and short form 36 (SF-36) were used to assess the quality of life. The physical disability was evaluated with the health assessment questionnaire (HAQ). The reliability of the SCQ scale was assessed by test-retest reliability. For construct validity, the correlations of SCQ with the HAQ, SF-36, PsAQoL, age, body mass index (BMI), disease duration, disease activity in psa (DAPSA), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Psoriasis Area and Severity Index (PASI), dactylitis and enthesitis were evaluated. The mSCQ was also used by removing the items related to rheumatic conditions. For the test-retest reliability of the Turkish version of SCQ, the intraclass correlation coefficient was 0.965, p 0.05). Although SCQ had a low correlation with DAPSA (rho = 0.262, p = 0.031), mSCQ was not correlated with DAPSA (p > 0.05). mSCQ was significantly correlated with BMI (rho = 0.233, p = 0.016), but SCQ was not (p > 0.05). The Turkish version of SCQ had adequate reliability and validity, and the mSCQ improved the validity of the scale in patients with PsA.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Health Sciences; ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Romatoloji; Rheumatology; Psoriatic arthritis; Comorbidity; Psychometrics; Questionnaires; CORRELATION-COEFFICIENTS; INFLAMMATORY ARTHRITIS; REPORTED OUTCOMES; INDEX; RELIABILITY; POPULATION; ENTHESITIS; MORBIDITY; DISEASES; SCQ; Psoriatic arthritis; Comorbidity; Psychometrics; Questionnaires